Comparison of fondaparinux with low molecular weight heparin for venous thromboembolism prevention in patients requiring rigid or semi‐rigid immobilization for isolated non‐surgical below‐knee injury. (10th October 2013) - Samama, C. M.; Lecoules, N.; Kierzek, G.; Claessens, Y. E.; Riou, B.; Rosencher, N.; Mismetti, P.; Sautet, A.; Barrellier, M.‐T.; Apartsin, K.; Jonas, M.; Caeiro, J. R.; et al.
Summary Background In several small studies, anticoagulant therapy reduced the incidence of venous thromboembolism (VTE) in patients with isolated lower‐limb injuries. Objectives To compare the efficacy and safety of fondaparinux 2.5 mg (1.5 mg in patients with a creatinine clearance between 30 and 50 mL min−1) over nadroparin 2850 anti–factor Xa IU. Patients and Methods In this international, multicenter, randomized, open‐label study, patients with an isolated non‐surgical unilateral below‐knee injury having at least one additional major risk factor for VTE and requiring, in the Investigator's opinion, rigid or semi‐rigid immobilization for 21–45 days with thromboprophylaxis up to complete mobilization received subcutaneously once‐daily either fondaparinux or nadroparin. The primary efficacy outcome was the composite of VTE (symptomatic or ultrasonographically detected asymptomatic deep vein thrombosis of the lower limb or symptomatic pulmonary embolism) and death up to complete mobilization. The main safety outcome was major bleeding. Results We randomized 1349 patients (mean age 46 years): 88.7% had a bone fracture, and 83.8% had a plaster cast fitted (mean duration of immobilization, 34 days). The primary efficacy outcome occurred in 15 of 584 patients (2.6%) in the fondaparinux group and 48 of 586 patients (8.2%) in the nadroparin group (odds ratio, 0.30; 95% confidence interval [CI], 0.15–0.54; P < 0.001). A single major bleed was experienced by fondaparinux‐treated patients and none by nadroparin‐treated patients. These results were maintained up to the end of follow‐up. Conclusions Fondaparinux 2.5 mg day−1 may be a valuable therapeutic option over nadroparin 2850 anti‐FXa IU day−1 for preventing VTE after below‐knee injury requiring prolonged immobilization in patients with additional risk factors.